2021
DOI: 10.1007/s10644-021-09347-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic determinants of remittances to India

Abstract: Migration and remittances have always been an exciting arena of research for economists around the globe. Remittance flows have evolved as a significant economic variable over the past decade. In several developing countries, remittances exceed the other capital inflows and value of total exports. Thus, it is widely recognised as a potential funding source for economic development in emerging economies. The inflow of remittances to India has increased tremendously in the recent past making the country the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
1
10
0
1
Order By: Relevance
“…In one such study by Gupta (2005) in the context of India, it was found that an increase in the number of emigrants, migrant income and the economic condition in the host country are the major factors that decide the amount of remittance to be sent to the home country. In another study for India by Jijin et al (2022), it was found that the exchange rate, oil prices and altruism are the major remittance drivers. This result also coincided with the determinants of remittance in the case of Egypt (Akçay and Karasoy, 2019).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…In one such study by Gupta (2005) in the context of India, it was found that an increase in the number of emigrants, migrant income and the economic condition in the host country are the major factors that decide the amount of remittance to be sent to the home country. In another study for India by Jijin et al (2022), it was found that the exchange rate, oil prices and altruism are the major remittance drivers. This result also coincided with the determinants of remittance in the case of Egypt (Akçay and Karasoy, 2019).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Besides government policy, there is a number of macroeconomic determinants influencing remittance flows, among which are the level of economic activity both in the host country and the Motherland, including "domestic income, the wage rate, the rate of inflation, black market exchange rates, interest rate differentials, secure means of transferring remittances, and the efficiency of the banking system" (Buch et al, 2002, p. 6). Also, the number of migrant workers abroad, the share of temporary migrants in total migrants, and their wages are determinants of worker remittances (Bunduchi et al, 2019;Hina and Ullah, 2021;Jijin et al, 2022) In addition to these macroeconomics, Buch et al (2002) list the following microeconomic determinants: (i) the education and the income level of the migrant and his family, (ii) the length of actual or expected stay of the migrant abroad, (iii) the number of dependents at home, and (iv) marital status.…”
Section: Monetary Remittancementioning
confidence: 99%
“…6). Такође, детерминанте дознака радника су и број радника миграната у иностранству, удео привремених миграната у броју укупних миграната, као и њихове зараде (Bunduchi et al, 2019;Hina & Ullah, 2021;Jijin et al, 2022). Осим ових, макроекономских, Buch et al (2002) наводе следеће микроекономске детерминанте: (i) образовање и ниво прихода мигранта и његове породице, (ii) дужина стварног или очекиваног боравка мигранта у иностранству, (iii) број издржаваних лица код куће, и (iv) брачни статус.…”
Section: новчане дознакеunclassified
“…Existing literature focused on remittances has produced two lines of research direction. First, many researchers have investigated the role of remittances in the economy by taking micro, and macro aspects (Barnabà et al, 2021;Nwogu, 2021;Anzoategui et al, 2011;Azizi, 2018), while another line of findings has revealed the key determents for increases and decreases of foreign remittances in the economy (Ojede et al, 2019;Bhatt and Kharel, 2021;Jijin et al, 2021;Bunduchi et al, 2019). Refers to macro determinants for remittances inflows in the economy, several factors have emerged, but with the change of the country's macrostructure, the role of macro determents differs accordingly (Ruiz and Vargas-Silva, 2009).…”
Section: Introductionmentioning
confidence: 99%